Hypercalcemic Encephalopathy due to Ectopic Parathyroid Adenoma in an Elderly Woman - Parth Sharma; Monica Gupta; Ambadas Rathod; Puneet Kaur; Sudhansoo Khanna (Journal of the Indian Academy of Geriatrics)
Hypercalcemia leads to serious neurological manifestations due to the modulation of neurotransmitters by high calcium levels. Hypercalcemia secondary to primary hyperparathyroidism attributable to an ectopic parathyroid adenoma is a rare clinical entity. The exact localization of the ectopic lesion can be challenging for clinicians, requiring a multimodal approach. An elderly female presented to our emergency department in an irritable state, followed by altered consciousness. The serum calcium, phosphorus, and serum intact parathormone levels were >14 mg/dL, 2.3 mg/dL, and 428 pg/mL, respectively. After a series of investigations, technetium-99m sestamibi parathyroid scintigraphy clinched the diagnosis of a MIBI-avid lesion, a 19 mm × 14 mm × 23 mm parathyroid adenoma at the T2–T3 vertebral level, anteromedial to the left common carotid artery. The high calcium levels were initially managed with aggressive fluid resuscitation with intravenous normal saline. This was followed by complete excision of the parathyroid adenoma. Our case report highlights the importance of an early identification of potentially reversible etiologies of hypercalcemia and elucidates an approach to physicians regarding hypercalcemic encephalopathy.